Pathology, infectious agents and horse‐ and management‐level risk factors associated with signs of respiratory disease in Ethiopian working horses. (2nd October 2020) - Laing, Gabrielle; Christley, Robert; Stringer, Andrew; Ashine, Tibebu; Cian, Francesco; Aklilu, Nigatu; Newton, Richard; Radford, Alan; Pinchbeck, Gina
Abstract: Background: Respiratory disease is a common cause for presentation of working horses to clinics in Ethiopia and a priority concern for owners. Objectives: To identify risk factors for and association of pathogens with respiratory signs in working horses. Study design: Unmatched case‐control study. Methods: Cases were those animals recently coughing (last 7 days) or observed with coughing, nasal discharge or altered respiration at the time of examination. A physical exam and respiratory endoscopy were performed including a tracheal wash sample to detect the presence of pathogens and serology performed on blood. An owner questionnaire was administered. Risk factors were determined using multivariable logistic regression. Results: Data on 108 cases and 93 unmatched control horses were obtained. Case horses often had underlying lower airway pathology and were significantly more likely to have Streptococcus zooepidemicus detected (OR: 12.4, 95% CI: 3.6‐42.4). There was no evidence of a major role for viral respiratory pathogens. Risk factors included completion of strenuous work (OR: 2.7, 95% CI: 1.2‐6.3), drinking from stagnant water sources (OR: 2.3, 95% CI: 1.0‐5.2) or being housed on a cobbled floor (OR: 2.0, 95% CI: 1.1‐3.8). There were increased odds of respiratory disease in young and old horses in this population. Main limitations: Samples for pathogen detection and cytology were only taken from the trachea. Conclusion: S. zooepidemicus, a common commensal, may play a role in clinical respiratory disease in this population.